2019
DOI: 10.31557/apjcp.2019.20.9.2723
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-215 as a Diagnostic Marker in Egyptian Patients with Hepatocellular Carcinoma

Abstract: Background: MicroRNAs are mentioned as a small non-coding RNAs groups and aberrant miRNA expression was found in hepatocellular carcinoma (HCC) patients. Aim: To evaluate role of plasma MicroRNA-215 as a diagnostic tool in HCC patients. Methods: A prospective study included 195 subjects: healthy controls (group I), cirrhotic patients (group II), and patients with HCC (group III). Clinical examination, radiological and laboratory investigations which included quantification of miR-215 by Real-time qPCR were don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…6 Hepatocellular carcinoma incidence is rising all over the world due to a rise in the incidence of HBV and HCV infection and increased prevalence of non-alcoholic fatty liver disease. 7 As classified by the WHO, the world can be divided into three types of area according to the prevalence of chronic HBsAg carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Hepatocellular carcinoma incidence is rising all over the world due to a rise in the incidence of HBV and HCV infection and increased prevalence of non-alcoholic fatty liver disease. 7 As classified by the WHO, the world can be divided into three types of area according to the prevalence of chronic HBsAg carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, treatments for chronic HBV infection have been updated and their efficiency improved 6 . Hepatocellular carcinoma incidence is rising all over the world due to a rise in the incidence of HBV and HCV infection and increased prevalence of non‐alcoholic fatty liver disease 7 …”
Section: Introductionmentioning
confidence: 99%
“…And Shaker et al found the incidence of HCC in Egypt is overall increasing, from 4% in 1993 to 7.3% in 2003 [67]. Besides, the incidence rate of HCC among the cirrhosis patients in Egypt was approximately 21% [41], which might play an important role in the diagnosis of HCC. In addition, Yang, Y et al found the miRNAs had higher diagnostic efficacy in Asians with 22 DOR than Caucasians [72].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 As a malignant tumor disease, studies have shown that a variety of factors are involved in the complex development of liver cancer, 3 and its highly metastatic and invasive nature is a multistep process. 4 However, the cause of the disease is still unclear. Studies have shown that miRNAs have a variety of biological functions related to cancer progression, including cell survival, proliferation, and migration, and are closely related to the development of various tumors.…”
Section: Introductionmentioning
confidence: 99%